2019
DOI: 10.1096/fj.201802279r
|View full text |Cite
|
Sign up to set email alerts
|

Physioxic human cell culture improves viability, metabolism, and mitochondrial morphology while reducing DNA damage

Abstract: Multicellular organisms balance oxygen delivery and toxicity by having oxygen pass through several barriers before cellular delivery. In human cell culture, these physiologic barriers are removed, exposing cells to higher oxygen levels. Human cells cultured in ambient air may appear normal, but this is difficult to assess without a comparison at physiologic oxygen. Here, we examined the effects of culturing human cells throughout the spectrum of oxygen availability on oxidative damage to macromolecules, viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Studies in 2D cell line cultures indicated an optimal physioxic range low enough to reduce oxidative damage but high enough for efficient oxidative metabolism for different cell types. ( Ferguson et al, 2018 ; Timpano et al, 2019 ). Finding an optimal oxygen concentration that mirrors the in vivo physiological range in colon (<1%–3%), might require some optimization depending on the type of experiments, organoid density and differentiation protocol used.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in 2D cell line cultures indicated an optimal physioxic range low enough to reduce oxidative damage but high enough for efficient oxidative metabolism for different cell types. ( Ferguson et al, 2018 ; Timpano et al, 2019 ). Finding an optimal oxygen concentration that mirrors the in vivo physiological range in colon (<1%–3%), might require some optimization depending on the type of experiments, organoid density and differentiation protocol used.…”
Section: Discussionmentioning
confidence: 99%
“…Here we provide detailed evidence of intertumoral heterogeneity at the transcriptional level by performing in vitro hypoxia studies using several human-derived cell lines, which allowed us to identify a robust common hypoxia signature ( Figure S1d ), despite the heterogeneity. Importantly, we used 5% O 2 as a physiological oxygen control, rather than 21% O 2 , more accurately representing the in vivo oxygenation levels, which can influence viable cell number, metabolism, and mitochondrial function [ 13 ]. By analyzing differential gene expression at three different oxygen concentrations ( Figure 1 b), it is clear that the vast majority of transcriptional changes had already occurred under physioxia, with a very modest number of genes differentially regulated between 5% O 2 and 1% O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Tumor hypoxia drives malignancy by promoting chemo-and radiotherapy resistance, an immunosuppressive microenvironment, cancer cell stemness, angiogenesis, and metabolic modulation [9][10][11]. The study of tumor hypoxia in vitro frequently uses cell cultures exposed to atmospheric conditions (21% O 2 ) as a control, although this does not represent any physiological oxygen fraction found in vivo [12] and does not always recapitulate cellular functions under physioxia [13]. Physiological oxygen availability is tissue-dependent, with 2%-9% O 2 (10-40 mmHg) being reported for the healthy brain [14].…”
Section: Introductionmentioning
confidence: 99%
“…Immunofluorescence and microscopy. Immunofluorescence and microscopy were performed as previously described (55). For mitochondrial shape and fusion, images were analyzed using Volocity (PerkinElmer).…”
Section: Methodsmentioning
confidence: 99%